Make your living trust (Nolo, 2025)
"A living trust is a powerful document that can help readers avoid probate, plan for incapacity, and provide for their loved ones. This book provides everything the reader needs to know about living trusts--from how to make one to where to store it when it's completed. This book includes key information about how living trusts work, who needs a living trust, how living trusts are different from wills, types of trusts, making a living trust with or without a lawyer, types of property that can go into a living trust, naming trustees and beneficiaries, transferring property, finalizing a living trust, and other useful estate planning tools"--